If you bite & devour one another : Biblical principles for handling conflict - Strauch, Alexander, 1944- (Littleton, Colo. : Lewis and Roth Publishers, 2011)
"Conflict in churches is a pervasive problem we know all too well. If You Bite & Devour One Another is the only book of its kind, examining all the biblical passages on conflict and outlining key scriptural principles for handling various kinds of conflicts among Christians--whether personal disputes, issues of Christian liberty in lifestyles, congregational matters, or disagreements about important doctrines. The book emphasizes Spirit-controlled attitudes and behaviors through solid Bible exposition and true-to-life stories of Christians handling real-life conflicts in a Christ-honoring way" -- BACK COVER.
Act in the Spirit -- Act in love -- Act in humility -- Control the anger -- Control the tongue -- Control the criticism -- Pursue reconciliation -- Pursue peace -- Face false teachers -- Face controversy -- Appendix: Understanding the word flesh.
Includes bibliographical references and indexes.
Keywords: Church controversies; Crkva -- Polemike; Conflict management -- Religious aspects -- Christianity; Rukovođenje konflikata -- Religijski aspekt -- Kršćanstvo; Međuljudski odnosi -- Sukobi